Typomorphology of Historical Old Mosques in Jakarta: Urban Islamic Heritage Preservation Strategy in Today's City Dynamics - Anisa Anisa; Wafirul Aqli; Jundi Jundullah Afgani; Irma Nurjannah; Muhammad Raufal Islamy (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Jakarta holds a variety of cultural and architectural heritage. One of the architectural heritages that can be traced to this day is the Mosque. There are several historical mosques that can be traced to this day, including the Angke Mosque, Al Arif Mosque, Ansor Mosque, Kampung Bandan Mosque, and Luar Batang Mosque. These mosques reflect a mixture of cultures and changes in social, religious, and architectural aspects. This study aims to explore and analyze the architectural characteristics of the five historical mosques in Jakarta. This study uses a qualitative method with typomorphological analysis that obtains data from field observations and literature. The results of the study show that each mosque has a distinctive spatial typology, influenced by a blend of local vernacular, colonial, and Islamic architectural traditions. Elements such as tiered roofs, wooden structures, open porch spaces, and the absence of domes reflect adaptation to the tropical climate and local building culture.